O instituto da ouvidoria como instrumento para a melhoria da gestão pública universitária: estudo de caso da ouvidoria geral da Universidade Federal do Espírito Santo - Alves, Juliana Cruz (2014)
In the context of Participatory Democracy, whose elements were inserted in the Brazilian Democracy by the 1988 Federal Constitution, by legitimating user participation in direct and indirect public administration providing mechanisms for social control, we emphasize the public ombudsman, and among them the university ombudsman, as mechanisms for dialogue and mediation between citizens and public institutions. Although there are important studies about public ombudsman, particularly in the health and judicial areas, there is still a lack of studies in public administration field when refering to specific studies on university ombudsman, leaving a gap that needs to be filled. Accordingly, the present research aimed to investigate the performance of the UFES's General Ombudsman, seeking to answer the question: How important is the UFES's General Ombudsman in UFES's public administration? And, along with that, bring up relevant and peculiar aspects of the university ombudsmen, which certainly reach, such as the UFES's General Ombudsman, other higher education public institutions's ombudsmen, giving greater visibility to an institute sometimes unknown or treated without due attention. Therefore, a qualitative research from the technical procedure of the case study was conducted, using documentary analysis, spontaneous observation and the application of interviews. Thus, in addition to addressing structural and cyclical aspects involving the Ombudsman, this work brings the perception of citizens who used the services of the agency, providing a magnification onto the discussion on the subject at the Academy, and perhaps inducing organizational changes.